1975
DOI: 10.1042/bj1500235
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal-muscle growth and protein turnover

Abstract: Because of turnover, protein synthesis and breakdown can each be involved in the regulation of the growth of tissue protein. To investigate the regulation of skeletal-muscle-protein growth we measured rates of protein synthesis and breakdown in growing rats during development on a good diet, during development on a marginally low-protein diet and during rehabilitation on a good diet after a period of severe protein deficiency. Rates of protein synthesis were measured in vivo with a constant intravenous infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
178
4

Year Published

1980
1980
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(208 citation statements)
references
References 33 publications
26
178
4
Order By: Relevance
“…In a growing animal, increased protein accretion rates are generally the result of both increased protein synthesis and, to a lesser degree, increased protein degradation rates (Millward et al, 1975;Houlihan and Laurent, 1987;Houlihan et al, 1988). However, in the present study, higher whole-body protein accretion rates were not accompanied by significantly increased protein synthesis or degradation rates.…”
Section: Effects Of Ogh On Body Composition Andcontrasting
confidence: 53%
“…In a growing animal, increased protein accretion rates are generally the result of both increased protein synthesis and, to a lesser degree, increased protein degradation rates (Millward et al, 1975;Houlihan and Laurent, 1987;Houlihan et al, 1988). However, in the present study, higher whole-body protein accretion rates were not accompanied by significantly increased protein synthesis or degradation rates.…”
Section: Effects Of Ogh On Body Composition Andcontrasting
confidence: 53%
“…Higher values (5 and 10%/day, respectively) have been observed for young males of either up to 1.4 kg (Palmer et al, 1980) or 2 to 2.5 kg BW (Laurent, 1982). FSR is known to be closely related to animal development (Laurent, 1982) and decreases with age (Millward et al, 1975;Lobley, 1993) and the multiparous does used in this study are considered adult animals. Lactation has a clear effect on mammary and liver tissues (Sampson et al, 1986), but effects on muscle are not yet confirmed.…”
Section: Discussionmentioning
confidence: 82%
“…Pron p 8 r p 0.41 P 1 0.05 tein concentration was determined using a modification of the folin-phenol method (Lowry et al 1951), and RNA concentration was estimated using dual-wavelength absorbance with an internal RNA standard, with blanks to confirm that the protocol was working (Ashford and Pain 1986). Fractional rates of protein degradation (k d , in percent per d) were calculated as (Millward et al 1975). RNA was expressed as…”
Section: Estimating Fractional Rates Of Protein Synthesismentioning
confidence: 99%